SISTEM PENDUKUNG KEPUTUSAN PENERIMA ZAKAT DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Asni Furoida; sutikno sutikno (Universitas Islam Sumatera Utara, 2017)
Zakat in Islam is a cleansing of wealth by setting aside some of it and then being distributed to mustahik. Zakat management becomes important thing to do in Indonesia because the majority of population in Indonesia is Muslim. One of zakat management institutions in Indonesia is Badan Amil Zakat Nasional (BAZNAS) Semarang. Zakat distribution from muzaki to mustahik in BAZNAS Semarang is distributed by utilization program, such as the Semarang Cerdas programs that focus on the distribution of funds in the field of education. One of Semarang Cerdas program provides educational assistance for orphans, du'afa and disadvantaged students that aim to alleviate the cost of education. The problem encountered is that the election of mustahik is still being done manually. This method often leads to miscalculations that result in less accurate of mustahik election. There are five criterias in determining mustahik; the status of children, family income, family responsibilities, house index, and ownership of property. The use of simple additive weighting method was chosen because this method is able to select the best alternative by calculating and considering the weight value of each criterion, and then proceed to determine the process of ranking the mustahik based on the amount of available fund. The test results showed that the accuracy of the new system with the old system of BAZNAS Semarang is 81%, so it could be concluded that this zakat recipient decission support system is able to process the mustahik election quickly and efficiently.